Readings in information retrieval (Morgan Kaufmann, 1997)
Information retrieval systems provide end-user access to the huge range of textual information resources that are now available. The techniques used are now being applied to multimedia retrieval, and to related information-seeking tasks such as information extraction and summarization. This collection contains papers covering both general theory and specific method, to offer a comprehensive view of the entire field. Each section consists of a carefully selected group of papers, together with a critical introduction to that topic and an extensive list of additional references.